2009
DOI: 10.1530/rep-08-0362
|View full text |Cite
|
Sign up to set email alerts
|

The role of IGF1 in the in vivo production of bovine embryos from superovulated donors

Abstract: IGF1 plays an important role in bovine follicular growth, acquisition of oocyte competence and embryo viability. Current data also indicate a critical role for IGF1 in both the ovarian response and the embryo yield following the superovulatory treatments. IGF1 can have either positive or negative effects on embryo viability which is related to the concentration of IGF1 induced by superovulation treatment. These effects impact either on oocyte competence or directly on the embryo. Concentrations in the physiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 257 publications
(157 reference statements)
5
35
0
2
Order By: Relevance
“…This is in agreement with Velazquez et al (24), who stated that higher doses of IGF-1 induce downregulation of IGF-1 receptors.…”
Section: Discussionsupporting
confidence: 93%
“…This is in agreement with Velazquez et al (24), who stated that higher doses of IGF-1 induce downregulation of IGF-1 receptors.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, in a naturally occurring high IGF1 microenvironment such as with PCOS (Thierry van Dessel et al 1999), the embryos are continuously exposed to abnormally high levels of IGF1, which may exacerbate the phenotype observed in our in vitro model (high apoptosis and hypertrophic ICM). Furthermore, given that oestrogens regulate to a great extent IGF1 production in the uterus (Velazquez et al 2009), an increased paracrine action of IGF1 caused by the greater bioavailability of free oestrogens present in the endometrium of PCOS women (Leon et al 2008) would lead to an impaired endometrial function (Lathi et al 2002, Giudice 2006) that would further reduce chances of normal pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin bind to cell surface receptor and its action is receptor-mediated. It has been demonstrated that insulin stimulates glucose and amino acid uptake and protein synthesis (Harvey and Kaye, 1988;Kane et al, 1997) of mouse embryos (Velazquez et al, 2009;Kaye and Harveyt, 1995). Several studies have indicated that insulin increases the in vitro oocyte maturation and development of human (Dashtizad et al, 2003), mice (Demeestere et al, 2004) and porcine embryos .…”
Section: Introductionmentioning
confidence: 99%